Bilingual-Based Digital Story Telling Innovation to Grow the Pancasila Student Profile for Primary School - Umar, Fadilah; Khosiyono, Banun Havifah Cahyo; Irfan, Muhammad (Universitas Pendidikan Mandalika, 2023)
Educators must adapt contextual teaching models with educational technology to improve the quality of teaching and learning English. Digital storytelling is a meaningful technology that can improve the quality of literacy and develop student character.This study was a need analysis study as a part of the research and development of developing bilingual-based digital storytelling to grow the Pancasila student profile. This study aimed to explore students’ and teachers’ needs for bilingual-based digital storytelling to realize Pancasila Student Profile for primary school. This research was qualitative mixed-method research. Data collection techniques using document analysis, questionnaires, and interviews. The research participants were 29 students and 3 teachers of Indonesian Primary Schools. Findings show that the results of students’ and teachers’ need state that it is necessary to develop English digital storytelling to realize Pancasila students profil for Primary School. The majority of students who have an interest in carrying out learning can use bilingual-based digital telling story-learning media. This study aids researchers and teachers in Indonesian primary schools in innovating Bilingual-based Digital Story Telling to Grow the Pancasila Students Profile in Elementary School Students.